Enhancing sustainable development practices in the Malaysian construction industry: sustainable built environment, sustainable project management, and sustainable construction / Hasmawiah Mad Kaidi ... [et al.] - Mad Kaidi, Hasmawiah; Hassan, Fadzil Padzil; Mohammad, Hairuddin; Ismail, Noor Akmal Adillah; Kamil, Mohd Dhiya Hafreez (UiTM Press, 2025)
Despite efforts to promote the adoption of Sustainable Development (SD) concepts in Malaysian construction projects, an often-overlooked element is the potential misinterpretation of Sustainable Built Environment (SBE), Sustainable Project Management (SPM), and Sustainable Construction (SC) and the relevancy within the context of SD. This misconception and the risk of fragmented knowledge leading to misguided strategies, inefficient resource allocation, and sub-optimal project outcomes. This paper provides insights from research aimed at addressing these concerns by redefining the concepts of SBE, SPM, and SC to enhance understanding of application in SD which SBE guides overarching planning, SPM applies sustainable practices to individual projects, and SC ensures eco-friendly building practices during construction. Employing a qualitative approach for the research method, in-depth literature analysis was conducted using multi-layered thematic analysis by reassessing the right understanding of these concepts by identifying their similarities, differences, and overlaps. The findings suggest that a sound understanding of the concepts must be the principal starting point for learning SD in the built environment. The concepts should be perceived as a cohesive entity to avoid misconceptions in knowledge and practices as well as the industry practitioner can take proactive steps to foster a more sustainable and resilient construction sector, benefiting not only the construction industry but also society and the environment at large.